2017
DOI: 10.1155/2017/1909101
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Medical Foods Provide a High Dietary Acid Load and Increase Urinary Excretion of Renal Net Acid, Calcium, and Magnesium Compared with Glycomacropeptide Medical Foods in Phenylketonuria

Abstract: Background. Skeletal fragility is a complication of phenylketonuria (PKU). A diet containing amino acids compared with glycomacropeptide reduces bone size and strength in mice. Objective. We tested the hypothesis that amino acid medical foods (AA-MF) provide a high dietary acid load, subsequently increasing urinary excretion of renal net acid, calcium, and magnesium, compared to glycomacropeptide medical foods (GMP-MF). Design. In a crossover design, 8 participants with PKU (16–35 y) provided food records and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 35 publications
2
43
2
Order By: Relevance
“…The AA and mineral content of the analyzed diets are described in Tables and , respectively. Calculation of the potential renal acid load of the four diets, as previously described (Stroup et al ), suggested that the dietary acid load of the BAA diet was reduced to nearly neutral compared to the high‐acid AA diet (Fig. A); the casein diet was neutral and GMP diet was alkaline.…”
Section: Methodsmentioning
confidence: 82%
See 4 more Smart Citations
“…The AA and mineral content of the analyzed diets are described in Tables and , respectively. Calculation of the potential renal acid load of the four diets, as previously described (Stroup et al ), suggested that the dietary acid load of the BAA diet was reduced to nearly neutral compared to the high‐acid AA diet (Fig. A); the casein diet was neutral and GMP diet was alkaline.…”
Section: Methodsmentioning
confidence: 82%
“…In addition, femurs from Pah −/− mice are weaker and show lower bone mineral content (BMC) than femurs from WT mice, and this bone phenotype is exacerbated by the low‐Phe, high‐acid AA diet (Solverson et al ). In eight human subjects with PKU, we demonstrated threefold greater renal net acid excretion with ingestion of high‐acid AA medical foods, which could be ameliorated by ingestion of the low‐acid GMP medical foods (Stroup et al ). In this same study, proteinuria and hyperexcretion of urinary creatinine were observed in 38–63% of subjects with PKU with self‐reported lifelong compliance with high‐acid AA medical foods (Stroup et al ).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations